Augmenting home entertainment with digitally delivered touch - Spence, C; Gao, Y (SAGE Publications, 2024)
In this narrative review, we take a critical look at the various attempts that have been made to augment home (or personal) entertainment experiences via the addition of some form of digitally controlled tactile stimulation. There has been an explosive growth in the market for home entertainment in recent years, and a majority of smartphones and other wearable electronic devices are now touch-enabled. As such, it is important to consider the challenges and potential opportunities for enhanced multisensory entertainment that may result from the introduction of tactile/haptic stimulation in the context of audiovisual digital storytelling and/or gaming. The key technological, financial (and legal), cognitive, and creative/artistic, challenges associated with the tactile augmentation of home entertainment experiences are outlined. Tactile augmentation, in the sphere of both public and personal entertainment, is more likely to succeed when it goes beyond the merely pleonastic vibrotactile reproduction of those interactions/events than can already be seen and/or heard on screen. At the same time, however, it remains uncertain under what conditions immersion in an entertainment experience will be enhanced by the addition of some form of primitive digital tactile stimulation. Ultimately, until a clear usage case can be made for the benefits of introducing a tactile element to home entertainment, it is unlikely to gain traction and switch from being merely a gimmick to more of a valuable element of multisensory storytelling.